Rule Based System in E-Commerce Dolanan Bocah Pinter - Intan Oktaviani; Vihi Atina (Proceeding of International Conference on Science, Health, And Technology, 2021)
The development of information technology during the industrial revolution 4.0, the existence of the internet is very much needed by the community. The sales and purchasing process is no exception. SMEs Dolanan Bocah Pinter is SMEs making educational toys for kindergarten children. Various types of educational toys have been produced. The selling and buying process currently running is face-to-face between the seller and the buyer. For the promotional media for SMEs Bocah Pinter, they still use the conventional method, namely by distributing brochures and catalogs to kindergarten schools. This is an obstacle to the development of SMEs Bocah Pinter. Because buyers are only from local residents. With these problems, E-commerce was designed by implementing a Rule Based system. For the system development method using the RAD method. SWOT analysis is used to analyze business processes and PIECES analysis for weakness analysis of the running system compared to the system to be developed. E-commerce design is expected to help SMEs Bocah Pinter in developing its business, it is hoped that buyers will not only come from the surrounding community but from various regions.